Conversion to Gastrojejunostomy Tubes in Developmentally Disabled Children Intolerant to Gastrostomy Tube Feeding. Issue 3 (September 2019) - DeRaddo, Joseph S.; Skummer, Philip; Rivera, Marcus; Kobayashi, Katsuhiro
Abstract : ABSTRACT: This study retrospectively evaluated the safety, impact on growth, and clinical outcomes of gastrojejunostomy tubes (GJTs) converted from surgically placed gastrostomy tubes (GTs) in 44 developmentally disabled children (median age: 28 months). The total duration of GJT follow-up was 31, 378 device-days (median: 643 device-days). Three major complications (aspiration pneumonia) were identified in 3 patients (6.8%), 63 minor complications in 31 patients (70.5%), and 202 tube maintenance issues (TMIs) in 41 patients (93.2%). A significantly increased average change in weight-for-age z -scores was observed at each 6-month interval that continued past 25 months. Patients above the median rate of TMIs had marginally significant lower z -scores across the study period ( P = 0.06), compared with those below the median rate. GJTs were removed in 6 patients (13.6%) because of adequate oral intake at last follow-up. Conversion from GTs to GJTs was a viable option to achieve sustained growth in developmentally disabled children. Frequency of TMIs may negatively impact their growth. Abstract : Supplemental Digital Content is available in the text